2019
DOI: 10.1111/cbdd.13421
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of human‐like Ca2+ channels and effects of Ca2+ channel blockers in Acanthamoeba castellanii

Abstract: The evolution of voltage-gated calcium channel (Cav) in eukaryotes is an area of interest for biologists worldwide. The CLAN CL0030 and its family Ion_Trans 2 PF 07885 have been known to be present in prokaryotes, but the origin of these ion channels in Acanthamoeba spp. is yet to be determined. We inferred the origin of primitive forms of two-pore channels like proteins, human-like Cav 1.1 of L-type, and Cav subunit alpha-2/delta-1 in Acanthamoeba spp. early during evolution. By in-depth investigation into ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Mitochondrial calcium accumulation has been studied in Acanthamoeba, but a channel system that allows Ca 2+ to get through the outer mitochondrial membrane in A. castellanii has not been explored previously [2] and the same is the case with our knowledge regarding the movement of this ion across the cell membrane. With the rationale that Ca 2+ ions play a vital role in Acanthamoeba spp., and the recently reported expression of human-like Ca 2+ ion-channels and the effects of Ca 2+ -channel blockers [3] in trophozoite forms of keratitis isolate of Acanthamoeba castellanii, we tested chelators of Ca 2+ ions in trophozoite forms of this protist pathogen. Our intention was to elucidate the role of extracellular Ca 2+ in the biology of Acanthamoeba spp.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Mitochondrial calcium accumulation has been studied in Acanthamoeba, but a channel system that allows Ca 2+ to get through the outer mitochondrial membrane in A. castellanii has not been explored previously [2] and the same is the case with our knowledge regarding the movement of this ion across the cell membrane. With the rationale that Ca 2+ ions play a vital role in Acanthamoeba spp., and the recently reported expression of human-like Ca 2+ ion-channels and the effects of Ca 2+ -channel blockers [3] in trophozoite forms of keratitis isolate of Acanthamoeba castellanii, we tested chelators of Ca 2+ ions in trophozoite forms of this protist pathogen. Our intention was to elucidate the role of extracellular Ca 2+ in the biology of Acanthamoeba spp.…”
mentioning
confidence: 99%
“…The eukaryotic cells have intracellular storage of Ca 2+ ions but these storage sites get depleted if Ca 2+ ions are not replenished from extracellular resources. Recent studies have reported that the depletion of cytosolic Ca 2+ by blocking human-like voltage-gated Ca 2+ channels and calmodulin in Acanthamoeba castellanii with the drugs loperamide [3], amlodipine and gabapentin [4] exert amoebistatic and amoebicidal effect in low and high doses respectively. However, the effects of Ca 2+ chelation in extracellular space in A. castellanii have not been tested yet.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As promethazine easily penetrates the blood–brain barrier and has a high margin of safety, it could be tested in animal models of AK and GAE. On the basis of the rationale of repurposing drugs that are already approved by drug-regulating authorities that target calcium channels, proteins like CaM and muscarinic receptor subtype mAChR1 in Acanthamoeba have been suggested to be tested in human trials in AK. , Successful results in AK and possibly GAE with promethazine and its structural analogs would encourage the repurposing of drugs that can speedily reach from bench to bedside in AK and possibly GAE.…”
Section: Conclusion and Future Directionsmentioning
confidence: 99%